Application of telemedicine system for older adults postoperative patients in community: a feasibility study - Wang, Quan-Peng; Chang, Wan-Ying; Han, Man-Man; Hu, Ye-Xiao; Lin, Sai-Sai; Gu, Ye-Chun (Frontiers in Public Health, 2024)
In response to the growing challenges posed by an aging society, a telemedicine system was developed specifically for elderly postoperative patients, and its effectiveness was thoroughly investigated. Methods: Between May 2020 and May 2022, a total of 88 elderly postoperative patients were enrolled and randomly allocated into an experimental group and a control group. The experimental group received telemedicine services after discharge, while the control group received conventional medical services following the traditional protocol. One month after discharge, various indicators were evaluated for both groups, including number of visits, medical expenditures, postoperative recovery, anxiety, depression and satisfaction. Results: The number of visits and medical expenditures of the experimental group were less than those of the control group [1 (0,1) vs 1 (1, 2), Z=-3.977, P<0.001; 25.25 (0.00, 277.40) yuan vs 174.65 (49.63, 446.10) yuan, Z=-2.150, P=0.032]. In both groups, there were 2 cases of incision infection respectively. No significant difference was observed between the two groups (Fisher χ², P=0.259). In both groups, there was no instance of incision bleeding, incision dehiscence, readmission, or reoperation. Additionally, there was no significant difference in physical status between the two groups at discharge and after discharge (66.06±8.92 vs 65.45±7.39 t= 0.287, P= 0.775; 73.33±9.97 vs 70. 91±7.50, t=1.202, P=0.235). And there was no significant difference in the change of physical status between the two groups after discharge [10.00(0.00,10.00) vs 5.00(0.00,10.00), Z=-1.077, P=0.281)]. There was no significant difference in body weight change between the two groups after discharge [1.05 (0.38, 1.60) Kg vs 0.80 (0.50, 1.43) Kg, Z=-0.265, P=0.791]. There was no significant difference in the levels of anxiety and depression between the two groups at discharge (45.64±8.10 vs 44.60±8.24, t=0.520, P=0.604; 48.33±8.46 vs 47.50±6.85, t=0.418, P=0.677). But the levels of anxiety and depression in the experimental group were lower than those in the control group after discharge (34.92±7.38 vs 39.03±8.42, t=-2.183, P=0.032; 37.86±7.29 vs 41.93±7.13, t=-2.281, P=0.025);The change of anxiety level and depression level of the experimental group were more than those of the control group [